Photometric Properties of Isolated Spiral Galaxies NGC 4800 and NGC 2715 - H. Ali, Sinan (Iraqi Journal of Science, 2023)
We have carried out multi color CCD surface photometry on the spiral galaxies NGC 4800 and NGC 2715 using 1.88 m optical telescope of Kottamia Astronomical Observatory. From these observations, the surface brightness, Ellipticity, position angle and color indices profiles are studied. Stellar populations in different regions of the galaxies are analyzed using color indices diagrams. We found that the galaxy NGC 4800 has a diffuse bright nuclear region and the asymmetry of the bar is due to the nonuniform distribution of dust in the galaxy. The color indices of the western inner spiral arm coincide with the corresponding mean color indices of the bar indicates that the stellar population of the bar is the same as that of the western spiral arm. The brightness of NGC 2715 remains constant at limited distance along the major axis. This may be attributed to the presence of a bar whose position angle is close to that of the galactic disk. This galaxy also showed reddening, and this is due to the presence of a huge amount of dust in the bulge to disk transition zone.